Pseudotumour of the lung caused by Mycobacterium malmoense infection in an HIV positive patient. Issue 2 (February 1994) - Yoganathan, K; Elliott, M W; Moxham, J; Yates, M; Pozniak, A L
Abstract : A case of pulmonary Mycobacterium malmoense infection presenting as a pseudotumour of the lung in a severely immunosuppressed HIV infected patient is reported.